PENGARUH KUALITAS INFORMASI, KEGIATAN PEMASARAN DAN REPUTASI MEDIA SOSIAL TERHADAP KEPERCAYAAN DAN KETERLIBATAN POLITIK GENERASI Z - Timothy Jordan Halomoan; Muhammad Akbar Nugroho; Renny Risqiani (FEB Universitas Sam Ratulangi Manado, 2023)
Abstract. This study aims to analyze the relationship between information quality, marketing activities and social media reputation on trust and political involvement of Generation Z. Data collection as a source of research data is primary data. Will be collected based on the information of the respondents with direct observation in the field using a questionnaire according to the research variables. The data collection method will be in the form of an online questionnaire via Google Form. Respondents will receive a link via the Google form which contains a collection of questions that require responses. Respondents in this study were social media users and were in the 2003-2007 birth range with the sample technique used was purposive sampling. By using the Google form as data collection, 408 respondents were collected. The results showed that if the quality of social media information has increased, it will also increase the social media reputation, trust, and political involvement of generation Z. In addition, if the social media reputation has increased, then automatically directly increase trust. On the other hand, it is also known that increasing social media marketing activities will also increase trust, social media reputation, and political engagement. It is also known, if trust increases, it will also increase political involvement